ISTAT DATA UTILIZATION TO ENHANCE LANDSAT 8 IMAGES CLASSIFICATION PROCESS (GEOmedia, 2015)
ISTAT geographic data, updated to realize census 2010 project in October 2011, represents an useful resource to improve the results derived from Land cover/use cartography or satellite image processing. In fact, both ISTAT vector data and other cartography data (i.e. satellite image classification) can be integrated to realize a product that can help to better understand land cover data especially in urban environment (i. e. urban sprawl), although it can't be considered a cartography product in a strict sense. This paper summarizes an experimental study based on a LANDSAT 8 image that cover completely 5 provinces in the north of Italy, where it's shown that ISTAT data, DEM and combine of NDVI and NDBI indices can improve the results of the satellite image classification process, especially in urban areas. Used SW: ARCGIS 10.1 for desktop (ArcInfo license) and ERDAS Imagine.